2022
DOI: 10.1021/acssuschemeng.1c08167
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Extracellular Electron Transfer of Geobacter sulfurreducens in Bioelectrochemical Systems Using N-Doped Fe3O4@Carbon Dots

Abstract: A nanomaterial−living cell biohybrid system is an efficient energy conversion method due to enhanced interactions between inorganic materials and bacteria. However, inefficient electron transfer at the interface of the biohybrid remains as a limiting factor. Herein, an inorganic−biologic hybrid was proposed by combining a typical electroactive bacterium, Geobacter sulfurreducens, and a highly conductive N-doped Fe 3 O 4 with a carbon dot shell (Fe 3 O 4 @CD) to boost energy conversion in bioelectrochemical sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…90 This cathode demonstrated more efficacy, and the superior functionality was accompanied by increased bioactivity, cellular adherence, and moderate biofilm resistance. 90 CDs promote the improved metabolism of S. oneidensis MR-1 due to the increase in intracellular electron generation, ATP level, active extracellular secretions, transmembrane, and EET. 89…”
Section: Advances Of Carbonaceous Biocathodes For Co2 Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…90 This cathode demonstrated more efficacy, and the superior functionality was accompanied by increased bioactivity, cellular adherence, and moderate biofilm resistance. 90 CDs promote the improved metabolism of S. oneidensis MR-1 due to the increase in intracellular electron generation, ATP level, active extracellular secretions, transmembrane, and EET. 89…”
Section: Advances Of Carbonaceous Biocathodes For Co2 Conversionmentioning
confidence: 99%
“…The zeta potential of the CDs was observed to be substantially connected with the effectiveness of bioelectricity generation. Recently, an inorganic-biologic hybrid was investigated to improve energy conversion in MES by merging a typical electroactive bacterium, Geobacter sulfurreducens, and a highly conductive N-doped Fe3O4 with a CDs shell 90 . This cathode demonstrated more efficacy, and the superior functionality was accompanied by increased bioactivity, cellular adherence, and moderate biofilm resistance 90 .…”
Section: Carbon Dots (Cds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the peak at 1712 cm −1 attributed to CvO stretching vibrations was observed, 40,41 indicating that there are various oxygen-containing functional groups on the surfaces of all the CDs. In addition, an obvious absorption peak at 1580 cm −1 is caused by aromatic CvC skeletal vibration, 42,43 demonstrating that in the acid oxidation process, saccharides are dehydrated to form CvC serving as the elementary unit of CDs. 32 This finding corresponds to the results drawn from TEM and Raman spectroscopy.…”
Section: Morphological and Structural Characterization Of Cdsmentioning
confidence: 99%
“…Nevertheless, most of the hybrid materials are reported without any details on how they carry drugs to the target site, and are prepared via complicated processes along with the costly design. Some studies have reported the combination of CDs and Fe 3 O 4 nanohybrids, which exhibit superior and multi-functional features on detecting particular compounds such as doxycycline, 45 Geobacter sulfurreducens , 46 bacteria, 47 and metals. 47,48 However, integrative studies on the evaluation of naproxen release from the nanohybrid and its potential delivery have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%